2016
DOI: 10.3758/s13414-016-1114-7
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ discrimination of shapes from shading and cast shadows

Abstract: Shadows are powerful cues in the perception of shapes. We can perceive shading and cast shadow implicitly. We investigated infants' ability to detect a single discrepant figure that was depicted by shading or cast shadow and examined the influence of the contrast polarity of shadows on this process. In Experiment 1, we manipulated the blur direction of a shadow to create stimuli that appeared either to be partially shaded or to cast a shadow and then used a preference to test whether this difference would allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As we have noted, the special ambiguity of blues may reflect experience with light and shading in the natural environment. Developmental studies suggest that infants can begin to disambiguate shadows by the age of about 7 months (e.g., Granrud, Yonas, & Opland, 1985;Sato, Kanazawa, & Yamaguchi, 2016). However, little is known about how, or how long, it takes children to learn about the correlations between color and shading, and how this might influence their color percepts.…”
Section: Applying the Fpvs Approach To High-order Color Perception: Smentioning
confidence: 99%
“…As we have noted, the special ambiguity of blues may reflect experience with light and shading in the natural environment. Developmental studies suggest that infants can begin to disambiguate shadows by the age of about 7 months (e.g., Granrud, Yonas, & Opland, 1985;Sato, Kanazawa, & Yamaguchi, 2016). However, little is known about how, or how long, it takes children to learn about the correlations between color and shading, and how this might influence their color percepts.…”
Section: Applying the Fpvs Approach To High-order Color Perception: Smentioning
confidence: 99%
“…As far as we know, their study is the first to investigate infants’ cast shadow perception; however, their finding of 5-month-old infants’ sensitivity to cast shadow was not replicated in later studies [2427]. In the current study, we revealed that 7- to 8- month-old infants showed a preference for the unnatural lightness change of a duck in cast shadows, suggesting that infants at this age, at least, can detect a violation of their assumption that cast shadow cause the surface of an object to dim.…”
Section: Discussionmentioning
confidence: 97%